Relationship between childhood trauma, parental bonding, and defensive styles and psychiatric symptoms in adult life - Waikamp,Vitória (2021)
Abstract Introduction A relationship between different types of childhood trauma, parental care, and defensive styles and development of psychiatric symptoms in adulthood is proposed in this study. Understanding the nature of this association is essential to assist psychotherapists who treat patients with a history of past trauma. This study aims to examine the associations between childhood trauma, parental bonding, and defensive styles and current symptoms in adult patients who sought care at an analytical psychotherapy clinic. Methods The sample comprised 197 patients from an analytically oriented psychotherapy clinic. Participants responded to four self-report instruments that assessed, respectively, presence and frequency of several types of early trauma, type of parental attachment, styles of defenses, and current symptoms encompassing a wide variety of psychopathological syndromes. Results Only 5% of patients reported not having experienced any traumatic experience in childhood. Several traumas such as emotional and physical abuse, emotional neglect, and physical neglect showed positive and significant associations with several dimensions of current symptoms, and also with parental bonding and defensive styles. When analyzed together with the other variables, defensive styles explained the level of psychological suffering caused by the symptoms. Conclusions This study offers additional support for understanding the associations between childhood trauma, parental bonding styles, and defense styles and the psychiatric symptoms of patients in analytically oriented psychotherapy.